Integrating Customary Criminal Law into National Criminal Justice Systems: Indonesia and South Africa in a Southern Criminology Perspective - Sitompul, Shalih Mangara; Khoiruddin, Aldi Rizki; Muhammad Rustamaji (Kosmik Hukum, 2026)
The urgency of integrating customary criminal law into the national legal system is increasing, especially in countries with legal pluralism such as Indonesia and South Africa. Both countries face challenges in accommodating customary criminal law that is alive and evolving in society, which is often subordinated by the colonial-based national legal system and modernization. This study uses a southern criminology approach based on the thinking of Antonio Gramsci to analyze the hegemony of national law over local law and fight for space for knowledge and legal traditions from the Global South in the criminal justice system. The type of research used is normative comparative legal research with the collection of secondary legal materials in the form of legislation, court decisions, academic literature, and international instruments related to the existence and treatment of customary criminal law. This research utilizes literature study techniques and qualitative analysis of legal documents, as well as a variety of juridical, sociological, and historical approaches combined with Gramscian hegemony analysis. The results of the study show that constitutional recognition in both countries has not resulted in ideal integration; customary criminal law tends to remain marginalized by national regulations and the modern legal system. However, with an integration model that places customary criminal law as part of the restorative justice process and recognition of legal pluralism, the prospects for harmonization are increasingly open towards a more just and inclusive national criminal justice system. This study emphasizes the need to strengthen the position of customary criminal law, political will, and legal education based on southern criminology.